Pengaruh Sumber Daya Manusia, Inovasi Teknologi Digital, dan Strategi Pemasaran Terhadap Pendapatan Usaha Mikro, Kecil, dan Menengah (UMKM) di Wilayah Medan Utara - Ahmad Rivai; Amin Hou; Mega Hernawati Harefa; Agus Susanto; Mhd Restu Razaq (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
This study aims to analyze the role of human resources, digital technology innovation, and marketing strategies in increasing the income of Micro, Small, and Medium Enterprises (MSMEs) in the North Medan region. A quantitative approach was employed, incorporating surveys and in-depth interviews with MSME actors. Primary data were collected using questionnaires developed based on key research variable indicators, and analyzed using multiple linear regression. The results reveal that all three variables have a significant influence on MSME income enhancement. From a managerial perspective, the findings emphasize the importance of strengthening human resource capacity through training, utilizing digital innovation in operational activities, and formulating data-driven marketing strategies to improve business competitiveness. This study contributes to the development of MSME business models based on digital technology and marketing strategies and serves as a reference for local governments and stakeholders in designing strategic policies to foster sustainable local economic growth. Keywords: MSMEs, human resources, digital innovation, marketing strategy, business income